Adaptive cruise control system for an electric go-kart - Dayananda, Roshanga Charith; Than Lin; Manukid Parnichkun; Bohez, Erik L.J. (Pathum Thani : Asian Institute of Technology, 2017)
There are lots of safety options available in automobile industry today. Among them the adaptive cruise control system gets a significant place because it is much advance and im- portant thing to the driver. In my capstone project; it is designed an electric go-kart and implementing the adaptive cruise control system. In here the go-kart can move with a set speed and if there is a car ahead going less speed than it, it will slow down or stop on a pre-defined distance. This system program was done by using c++ programming on to the PID controller. Ultra-sonic sensors are used to measure the obstacles in front of the go-kart. This go-kart was tested in outdoor and indoor places successfully.
A capstone project submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Engineering Mechatronics Engineering, School of Engineering and Technology
Capstone Project (B.Sc.)-Asian Institute of Technology, 2017
Keywords: Adaptive control systems; Automobiles -- Automatic control; Automated vehicles